1992
DOI: 10.1017/s0317167100042207
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and Glucose Metabolic Profiles in Asymmetric Parkinson’s Disease

Abstract: ABSTRACT:Patients with predominantly unilateral parkinsonian signs may provide a unique opportunity to evaluate the cerebral representation of cognitive functions characteristically affected in idiopathic Parkinson’s disease. Twenty hemiparkinsonian patients (ten left and ten right) and 10 healthy controls, matched for age and education, were studied with neuropsychological tests and positron emission tomography. Both right and left hemiparkinsonians evidenced impairments in visuospatial and verbal episodic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 32 publications
3
30
0
Order By: Relevance
“…These latter studies further diverge in the way the degree of asymmetry was defined. Eight studies based their classification on subjective history and examination (Barber et al 1985;Blonder et al 1989;Bowen 1976;Direnfeld et al 1984;Huber et al 1989;Mohr et al 1992;Schendan et al 2009;Villardita et al 1983), while others used a standardised scale, such as the Columbia Rating Scale or the Unified Parkinson's Disease Rating Scale (UPDRS). Among these, there are further differences in the cutoff-values that were applied.…”
Section: Methodological Issuesmentioning
confidence: 99%
See 3 more Smart Citations
“…These latter studies further diverge in the way the degree of asymmetry was defined. Eight studies based their classification on subjective history and examination (Barber et al 1985;Blonder et al 1989;Bowen 1976;Direnfeld et al 1984;Huber et al 1989;Mohr et al 1992;Schendan et al 2009;Villardita et al 1983), while others used a standardised scale, such as the Columbia Rating Scale or the Unified Parkinson's Disease Rating Scale (UPDRS). Among these, there are further differences in the cutoff-values that were applied.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…The second study showed that patients with left-sided symptom onset were more impaired on object recognition compared to patients with right-sided onset (Tomer et al 1993). The remaining eight studies did not reveal any differences between LPD and RPD patients (Agniel et al 1991;Bentin et al 1981;Clair et al 1998;Direnfeld et al 1984;Levin et al 1991;Mohr et al 1992;Spicer et al 1988;Viitanen et al 1994). Summary.…”
Section: ) Visuospatial Cognitionmentioning
confidence: 97%
See 2 more Smart Citations
“…Studies that have attempted to explore the relationship between cognitive impairments and the asymmetry of motor symptoms in PD have found contradictory results. While some studies reported no correlation between the laterality of motor symptoms and cognitive asymmetry scores [1,20], Tomer et al [33] found that initial symptoms on the left side of the body were associated with more pronounced cognitive decline. However, comparison of test results between patients with left-or right-sided onset of initial symptoms yielded comparable mean values under both stimulation conditions.…”
Section: Discussionmentioning
confidence: 99%